2020
DOI: 10.1149/ma2020-01472690mtgabs
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ions Influence on Shewanella Oneidensis MR-1 Adhesion to ITO Electrode and Enhancement Current Output

Abstract: The goal in this study is to enhance the efficiency of bacterial extracellular electron transfer (EET) in Shewanella. oneidensis MR-1 by enhancing adhesion to the electrode. Our results clearly show a major difference in attachment and behavior of S. oneidensis MR-1 for Ca2+, Pb2+, Cd2+, and Mg2+ compared to the control. The final microbial coverage, as measured by confocal microscopy and cathodic peak charge in cyclic voltammetry (Qpc), increases with increasing metal ion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It was reported that S. oneidensis MR-1 owned a special resistance to AgNPs compared with E. coli. 41 It was reported that S. oneidensis MR-1 grew well when treated with 207 mg L −1 Pb 2+ or 112 mg L −1 Cd 2+ , 88 in which concentrations the E. coli could not survive. 89 The effective bioreduction of Ag + in and around the bacteria might clarify why S. oneidensis MR-1 lived well under 215 μg L −1 Ag + , in which concentration E. coli could not survive and accumulate less Ag inside the cells as reported in a previous work.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that S. oneidensis MR-1 owned a special resistance to AgNPs compared with E. coli. 41 It was reported that S. oneidensis MR-1 grew well when treated with 207 mg L −1 Pb 2+ or 112 mg L −1 Cd 2+ , 88 in which concentrations the E. coli could not survive. 89 The effective bioreduction of Ag + in and around the bacteria might clarify why S. oneidensis MR-1 lived well under 215 μg L −1 Ag + , in which concentration E. coli could not survive and accumulate less Ag inside the cells as reported in a previous work.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It was reported that S. oneidensis MR-1 grew well when treated with 207 mg L –1 Pb 2+ or 112 mg L –1 Cd 2+ , in which concentrations the E. coli could not survive .…”
Section: Results and Discussionmentioning
confidence: 99%
“…More riboflavin production able reach when micronutrient added. In this research use metal ions in microgram per liter as micronutrient [17]. Microbial Fuel Cells have been much research and developed with various substrates, bacteria, electrodes, electrode modifications, chamber variations, etc.…”
Section: Power Densitymentioning
confidence: 99%
“…Efficiency in MFCs is determined for the energy content from substrates 15 . Microorganisms in the anode catalyze the substrate (electron donors) for the utilization by extracellular metabolism to the electrode surface 16–18 . MFCs are composed of anode and cathode with electrodes such as carbon felt, graphite, carbon cloth, and so on, and a proton exchange membrane (PEM) that separates anode and cathode.…”
Section: Introductionmentioning
confidence: 99%